Nesting biology of the Narrow-billed Woodcreeper (Lepidocolaptes angustirostris) in a southern temperate forest of central-east Argentina - Jauregui, Adrián (2019)
We present data on the nesting biology of the Narrow-billed Woodcreeper (Lepidocolaptes angustirostris) in a natural forest in central-east Argentina. A total of 18 nests were found during four breeding seasons (2015–2019; from September to January), located in cavities (natural, artificial and woodpecker cavities). The incubation period lasted 16 days and eggs were larger than those from northern populations. Nestlings stayed in the nest for 17 days and we could measure nestlings at two nests. Within the forest, nests were built in large native trees. Seven nests were successful, nine were depredated and two were abandoned. The average nest daily survival rate (DSR) was estimated as 0.96, giving a cumulative chance of nest survival in a nesting cycle of 24%. Our study provides the first estimate of the nest DSR for the species and new records on the nesting biology of a poorly known Neotropical bird.